2022
DOI: 10.1016/j.isci.2022.103757
|View full text |Cite
|
Sign up to set email alerts
|

miR-376a-3p and miR-376b-3p overexpression in Hutchinson-Gilford progeria fibroblasts inhibits cell proliferation and induces premature senescence

Abstract: Summary Hutchinson-Gilford progeria syndrome (HGPS) is a rare genetic disorder, in which an abnormal and toxic protein called progerin, accumulates in cell nuclei, leading to major cellular defects. Among them, chromatin remodeling drives gene expression changes, including miRNA dysregulation. In our study, we evaluated miRNA expression profiles in HGPS and control fibroblasts. We identified an enrichment of overexpressed miRNAs belonging to the 14q32.2-14q32.3 miRNA cluster. Using 3D FISH, we demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“… 40 Furthermore, analysis of miRNA expression profiles in HGPS fibroblasts and control fibroblasts has demonstrated that the accumulation of progerin can result in the overexpression of certain miRNA genes, which may be related to the effect of progerin on epigenetic modification. 41 These findings suggest that the introduction of progerin into tumor cells could potentially impact gene expression through alterations in epigenetic modifications, including dysregulation of microRNAs.…”
Section: Discussionmentioning
confidence: 99%
“… 40 Furthermore, analysis of miRNA expression profiles in HGPS fibroblasts and control fibroblasts has demonstrated that the accumulation of progerin can result in the overexpression of certain miRNA genes, which may be related to the effect of progerin on epigenetic modification. 41 These findings suggest that the introduction of progerin into tumor cells could potentially impact gene expression through alterations in epigenetic modifications, including dysregulation of microRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…Progerin-mediated functions at the protein level and their relationship with miRNA expression have also been described in recent studies [ 51 , 52 , 53 ]. A structure-based study has revealed that unfarnesylated progerin can form a disulfide bond with an Ig-like domain in the nuclear lamina.…”
Section: Dysfunctional Progerin Expressionmentioning
confidence: 93%
“…The Alphafold2-assisted docking structure showed that disulfide bond formation was promoted by a weak interaction between the groove of the Ig-like domain and the unfarnesylated C-terminal tail region of progerin, providing molecular insights into the abnormal interactions caused by progerin [ 51 ]. The evaluation of miRNA expression profiles in HGPS and normal fibroblasts revealed an enriched set of overexpressed miRNAs belonging to the 14q32.2–14q32.3 miRNA cluster and showed that inducing their overexpression in normal fibroblasts reduced cell proliferation and increased senescence, whereas inhibiting them in HGPS fibroblasts alleviated proliferation defects and senescence and reduced progerin accumulation [ 52 ]. Progerin overexpression induced notable changes in miRNA expression and confirmed that has-miR-59 (miR-59) was markedly upregulated in cells from patients with HGPS and in multiple tissues of an HGPS mouse model ( Lmna G609G/G609G ) [ 53 ].…”
Section: Dysfunctional Progerin Expressionmentioning
confidence: 99%
“…In an interesting study by Frankel et al the expression profiles of miRNAs in HGPS and control fibroblasts were performed. An enrichment of overexpressed miRNAs from the 14q32.2-14q32.3 miRNA cluster was found [62]. Using 3D FISH, the authors showed that the overexpression of these miRNAs was associated with chromatin remodeling at this specific locus in HGPS fibroblasts [62].…”
Section: Micro-rna-inhibitorsmentioning
confidence: 98%
“…An enrichment of overexpressed miRNAs from the 14q32.2-14q32.3 miRNA cluster was found [62]. Using 3D FISH, the authors showed that the overexpression of these miRNAs was associated with chromatin remodeling at this specific locus in HGPS fibroblasts [62]. The researchers focus on miR-376b-3p and miR-376a-3p, both of which are overexpressed in HGPS fibroblasts [62].…”
Section: Micro-rna-inhibitorsmentioning
confidence: 99%